2017
DOI: 10.3126/ije.v6i1.16864
|View full text |Cite
|
Sign up to set email alerts
|

Organic Carbon Stocks, Dynamics and Restoration in Relation to Soils of Agroecosystems in Ethiopia: A Review

Abstract: Soils represent the largest carbon pool and play important roles for carbon storage for prolonged periods in agroecosystems. A number of studies were conducted to quantify soil organic carbon (SOC) worldwide. The objective of this review was to evaluate organic carbon stocks, dynamics and restoration in soils of agroecosystems in Ethiopia. Soil data from 32 different observations, representing four different agroecosystems, were analysed. The mean SOC stocks in the four agroecosystems varied and ranged from 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
3
4
0
Order By: Relevance
“…However, our results were consistent with studies which showed that the establishment of enclosures on previously degraded semi-arid grassland increased the emission of CO 2 from soil [66, 67]. The high CO 2 flux rate in the older enclosures (> 20 years), could be due to the dominance of perennial grasses which have greater root biomass than annual grasses and forbs and produce more root exudates and substrates [67], which supported microbial respiration activities in soil.…”
Section: Discussionsupporting
confidence: 92%
“…However, our results were consistent with studies which showed that the establishment of enclosures on previously degraded semi-arid grassland increased the emission of CO 2 from soil [66, 67]. The high CO 2 flux rate in the older enclosures (> 20 years), could be due to the dominance of perennial grasses which have greater root biomass than annual grasses and forbs and produce more root exudates and substrates [67], which supported microbial respiration activities in soil.…”
Section: Discussionsupporting
confidence: 92%
“…The total SOC stocks at soil depth for the three land use systems in this study were within the range of SOC stocks reported for other similar systems in Ethiopia 50 . The upper layer (0-30 cm depth) SOC stock of FFI in this study area was higher than the mean SOC (65.2 Mg C ha -1 ) of Nitisol soil under agroforestry systems in Ethiopia 50 .…”
Section: Stockssupporting
confidence: 84%
“…The total SOC stocks at soil depth for the three land use systems in this study were within the range of SOC stocks reported for other similar systems in Ethiopia 50 . The upper layer (0-30 cm depth) SOC stock of FFI in this study area was higher than the mean SOC (65.2 Mg C ha -1 ) of Nitisol soil under agroforestry systems in Ethiopia 50 . The result of SOC in 0-30 systems cm depth in FFI was also higher than the 0-30 cm depth SOC recorded in Gununo watershed agroforestry practices 51 , and 0-30 cm depth SOC (60.8 Mg C ha -1 ) of Indonesia homegarden agroforestry system 52 .…”
Section: Stockssupporting
confidence: 84%
“…Detailed overview of different techniques employed in modern times for SOC determination is well presented by Chatterjee et al (2009). Despite the wide usage of the "traditional" Walkley and Black (WB) method, due to its procedural simplicity (Wang et al 2012), it has been heavily criticized due to its limitations, which include incomplete combustion, variations in oxidation of various forms of SOC by dichromate, high cost of chemicals used for the analysis, and considerable low efficiency in C determination (FAO 2001(FAO , 2007Gelman et al 2012;Amare et al 2013;Gebeyehu et al 2017). Nevertheless, more accurate, precise, and cost-effective measurement of SOC is required in C sequestration programs in terrestrial ecosystems in view of ensuring accurate quantification, verification, and monitoring of potential SOC stocks over time.…”
Section: Uncertainties In Soil Organic Carbon Studiesmentioning
confidence: 99%